O‘ZBEKISTONDA HAYVONOT OLAMINING MILLIY MAʼLUMOTLAR BAZASINI SHAKLLANTIRISH - Tuychi , Jurayev (Actual problems and prospects of the study of the fauna, 2025)
This article examines the current issues of systematization and digitization of information on the fauna of the Republic of Uzbekistan. The scientific, technological, institutional and financial problems encountered in the formation of a national database are analyzed. Also, proposals and recommendations are given to solve existing problems.